A surveillance study for climate change as an environmental education model in GCC countries - Al-Hashim, Abdullah bin Aqla; Chuxia Lin, Hamad Almebayedh, (Opción, 2020)
The study aims to investigate a surveillance study for climate change as an environmental education model in GCC countries (The Cooperation Council for the Arab States of the Gulf) via comparative qualitative research methods. As a result, the GCC countries should embrace research and consultations as core tools in improving and reversing the effects of climate change in the region. In conclusion, the GCC countries have to make the following changes to their operations for safeguarding the environment. These nations should prevent the indiscriminate release of polluted fluids by oil tankers; and pollution from aluminum, petrochemical and construction industries.